Impact of Regional Anesthesia for Restriction of Metabolic and Inflammatory Changes during Abdominal Surgery - P. A. Lyuboshevsky; A. V. Zabusov (Общая реаниматология)
Surgical intervention is associated with the development of endocrine, metabolic, and inflammatory changes that may give rise to postoperative complications. Objective: to evaluate the impact of regional anesthesia on the magnitude of these changes during and after abdominal surgery. Subjects and methods. One hundred and twenty patients were examined during elective lower abdominal operations. The patients were divided into groups according to the anesthetic modality: general anesthesia alone (n=40) and in combination with continuous epidural (n=40) and spinal anesthesia (n=40). Cortisol, glucose, lactate, interleukins 6, 8, and 10 concentrations and daily urinary nitrogen excretion were studied before, during, and after surgery. Results. The two regional anesthesia modalities lowered the degree of an increase in the concentrations of cortisol, glucose, and lactate in the perioperative period and restricted a rise in the concentrations of both proinflammatory and anti-inflammatory cytokines. Spinal and epidural anesthesia both reduced daily urinary nitrogen excretion. Epidural versus spinal anesthesia/analgesia assured better quality of postoperative analgesia and was attended by less significant hemodynamic disorders. Conclusion. Both spinal and epidural anesthesia restrict the perioperative rise in the concentrations of cortisol, glucose, lactate, and cytokines and suppress protein catabolism after abdominal surgery. Key words: regional anesthesia, abdominal surgery, cortisol, protein and carbohydrate metabolism, inflammatory response.